Οι ανάγκες πληροφόρησης των ασθενών που υποβάλλονται σε καρδιοχειρουργική επέμβαση και των οικογενειών τους πριν την έξοδο τους από το νοσοκομείο - Παναγή, Ανδρούλλα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Introduction: The increased complexity of cardiac surgery makes critical the development of the effective education and teaching of both patient and relatives and it is part of the complex purpose of the nursing practice. The hospital discharge planning of a cardiac patient provides an opportunity to both himself and to his family, to deal with any problems, real or potential, which often occur in the postoperative period, in order to ensure the safe return of the patient at home. Providing high quality information regarding the discharge increases the satisfaction of the care provided, improves the adaptation of the patient at home after the exit from the hospital and enhances the ability of patients and their families in dealing with situations. Purpose: The main purpose of this study is to investigate the information needs of patients undergoing cardiac surgery and their families in Cyprus, before the hospital discharge. Material - Method: This is a descriptive comparative and correlational study which includes validation of the tools to a Greek-Cypriot population. The sample of the study included 132 patients who underwent a cardiac surgery and were hospitalized in two major Cardiac Surgery Centres in Nicosia from the 1st of March 2014 until the 31st of October 2014. The sample also included 132 relatives of the patients. Data collection was done by using the Cardiac Surgery Patient Discharge Questionnaire and Cardiac Surgery Discharge Questionnaire for Families which were translated in the Greek language. To test the stability of the tools they were piloted on 20 patients and their relatives in order to check the reliability of test - retest with the Pearson correlation coefficient. Moreover, an assessment was made of the homogeneity of the questions of the questionnaires with reliability and internal consistency coefficient Cronbach alpha. To check the validity of the structure of the questionnaires a confirmative factor analysis was made. For independent variables of two parameters the criterion t was applied while for independent variables of more than two parameters, the one-way Analysis of Variance (one-way ANOVA) was applied.Results: The questionnaire on patients shows a good reliability rate (Pearson correlation> 0.9, p = 0.000, Cronbach's Alpha> 0.6) and validity. The questionnaire on relatives shows satisfactory reliability of the test (Pearson correlation> 0.6, p <0.005). In correlation made on the fields of the questionnaire for the relatives of patients the Cronbach's Alpha coefficient was not calculated because there is no variation in the participants' responses. The comparison which was made between the patients and their relatives showed that the need to provide discharge information is more important to the relatives rather than the patients (p <0.05). In the patients' group there were some differences regarding the comparison between the genders. Women seemed to believe that the information regarding emotions and follow up is more significant (p = 0.000). Age is also an important factor that determines how important the discharge information is especially for patients under the age of 60 who seem to have a greater need for information on physical activity (p = 0.000). In the comparison made between the spouses and children of patients seems that spouses consider the provision of information relevant to symptoms more important than for children (p = 0.020). Conclusions: The data results of this study revealed important information about the discharge information needs of patients who underwent cardiac surgery and their families. Providing discharge information appears to be more important to the family than the patients themselves.
Keywords: Cardiac surgery patient discharge questionnaire; Cardiac surgery discharge questionnaire for families; Cardiac surgery; Nursing practice; Cardiac patient; Hospital; Greek-Cypriot population; Postoperative period; Age; Quality information; Ανάγκες πληροφόρησης των ασθενών; Ανάγκες πληροφόρησης των οικογενειών; Καρδιοχειρουργική επέμβαση; Νοσηλευτικής πρακτική; Καρδιοχειρουργικός ασθενής; Χώρος νοσηλείας; Ελληνο-Κυπριακός πληθυσμός; Μετεγχειρητική περίοδος; Ηλικία; Ποιότητα πληροφοριών; Νοσοκομείο